Cosecha y poscosecha: labores y exigencias de poscosecha - Ospina Parra, Carlos Eduardo; Alzate Henao, Sandra Viviana; Machuca Henao, Yuly Marcela; Rodríguez Blandón, Jefersson Andrés; Cardona Cardona, Jorge Enrique; Valencia Montoya, Jorge Alberto; Cardona, William Andrés; Rodríguez Yzquierdo, Gustavo Adolfo; Bautista Montealegre, Luis Gabriel; Betancourt Vásquez, Mónica; Miranda Salas, Tatiana Camila; Bolaños Benavides, Martha Marina (Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2021)
Plátano-Musa sapientum